Failure investigation of boiler tubes : a comprehensive approach - Haribhakti, Paresh; Joshi, P. B., Dr; Rajendra Kumar (Scientist) (ASM International, 2018)
"Coal-fired power plants rely on a network of boiler tubes that would stretch several kilometers if placed end to end. These tubes operate under extreme conditions and, despite due care, fail from time to time, leading to forced outages. Failure Investigation of Boiler Tubes: A Comprehensive Approach is a detailed guide to understanding damage mechanisms and how to identify and control them. It covers operating principles and interactions, material properties and selection, characterization tools and techniques, and application challenges. It also includes information on water chemistry and life assessment, and presents several well-illustrated case histories"--